PENYULUHAN HUKUM PENCEGAHAN KENAKALAN REMAJA (NARKOBA, PERUNDUNGAN, MIRAS) PADA SISWA-SISWI SMP NEGERI 1 MERAUKE - Pieter, Salvadoris; Endom, Agustina Handayani Winingsih; Ayu, Cica Kusmira Sagita; Imkotta, Betsy Rachel; Fenetiruma, Raymond Paradeys (Sagu: Jurnal Pengabdian Masyarakat, 2025)
This community service initiative was motivated by the increasing vulnerability of adolescents in Merauke Regency to the dangers of narcotics, bullying, and alcohol abuse due to a lack of legal literacy. This activity aims to provide a comprehensive understanding of the law and foster preventive awareness among students at SMP Negeri 1 Merauke. The implementation method used a juridical-educational approach through the "LBH Pelita Kasih GPI Papua Masuk Sekolah" program, which involved collaboration between Musamus University academics and legal practitioners. The activity included field observations, literature studies, and interactive counseling using lectures, role-play simulations, and group discussions. The results of the community service demonstrated a significant increase in students' understanding of criminal sanctions under the Narcotics Law and the Child Protection Law, as well as the development of proactive attitudes to reject deviant behavior. The synergy between educational institutions and legal aid institutions has proven effective in addressing the legal literacy gap, creating a safe school environment and supporting the achievement of the Golden Indonesia 2045 vision.